Bollspelen i Johannes Schefferus Lappland. Fragment av nordiskt tidigmodernt idrottsliv med utblickar mot Island och de brittiska öarna - Lidström, Isak (Idrott, historia och samhälle, 2024)
Sports historians have argued that the type of ball games common in the British Isles, which were practiced by two teams and in which the ball was driven with sticks towards predetermined goals – i.e., hurling, shinty, bandy and hockey – were never played in early modern Sweden. By highlighting descriptions of ball games in Johannes Schefferus’s The History of Lapland (1674), a source previously ignored by sports historians, this article challenges such a claim. One of the games described by Schefferus has some similarities with the violent stick-and-ball game known in Icelandic sagas as knattleikr. Even greater similarities (such as the start of the game with a face-off and the goals consisting of lines on the short edges) emerge when the game is compared with the Scottish game of shinty. Thus, pre-modern Scandinavia does not appear to have been as isolated in terms of sports and games as has been suggested by Swedish sports historians.